(untitled) (Revista de Estudos da Linguagem, 2017)
Resumo: O objetivo deste trabalho é apresentar as relações de herança das construções de posse ou de objeto possuído, como as classifica Perini (2008), as quais exibem os papéis temáticos de possuído e possuidor em sua rede temática e podem ser ilustradas por sentenças como José tem um carro. Carvalho (2015), analisando textos dos séculos XIV ao XVI, observou que os verbos filhar, haver, ter e tomar, que integram essas construções de posse, também constituem sentenças que evocam o frame dos verbos psicológicos, como em José tem medo. A autora verificou também uma identidade sintática entre esses dois tipos de estruturas, embora as de posse sejam construções com verbos plenos (CVPs) e as que denotam eventos psicológicos sejam construções de sentimento com verbos leves (CSVLs). Partindo da Gramática de Construções de Goldberg (1995), segundo a qual as construções são as unidades básicas da língua e estão relacionadas umas às outras por links de herança, e das teorias que propõem uma estreita relação entre os verbos plenos e suas contrapartes leves (BRUGMAN, 2001; BUTT, 2003; BUTT; LAHIRI, 2013; MACHADO VIEIRA, 2003; SCHER, 2003), foram analisadas as relações de herança entre as construções de posse material e as de posse abstrata (CSVLs). Para verificar as extensões de sentido entre ambas foram consideradas as relações sintático-semânticas, a frequência e a história dos verbos e/ou da construção. A análise dos 442 dados encontrados nos corpora permitiu concluir que as CSVLs foram motivadas pelas CVPs. Palavras-chave: relações de herança; construções; verbos psicológicos; verbos leves; verbos plenos. Abstract: The aim of this paper is to present the inheritance relations of possession constructions or possessed object constructions (as classified by Perini, 2008). These constructions show the thematic roles of possessed and possessor in its thematic network and can be illustrated by sentences such as José has a car. As Carvalho (2015) analyzed texts from 14th to 16th centuries, she noted that the verbs filhar (adopt), haver (there to be), ter (have) and tomar (take), which compose these possession constructions, also integrate sentences that evoke the frame of psych verbs like in José has fear. The author also found a syntactic identity between these two types of structures, although the possession constructions are heavy verb constructions (HVCs) and the constructions denoting psychological events are constructions of feelings with light verbs (CFLVs). Starting from Goldberg’s Construction Grammar (1995), according to which constructions are the basic units of a language and are related to each other by inheritance links, and from theories that suggest a close relationship between heavy verbs and light verbs (BRUGMAN, 2001; BUTT, 2003; BUTT; LAHIRI, 2013; MACHADO VIEIRA, 2003; SCHER, 2003), we analyzed the inheritance relations between material possession constructions and the CFLVs called constructions of abstract possession. To analyze extensions of meaning between them, the syntactic-semantic relations, the frequency and the history of the verbs and / or construction were considered. The analysis of 442 possession constructions found in the corpora made it possible to conclude that the CFLVs were motivated by HVCs. Keywords: inheritance relations; constructions; psych verbs; light verbs; heavy verbs.